Current Perspectives on Less-Known Aspects of Headache 2017
DOI: 10.5772/66624
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Smartphone Use and Unilateral Ocular Pain and Headache

Abstract: Ocular pain and headache may stem from many causes, ranging from infections and inflammations to radiating pain. Nowadays, use of smartphones may be an emerging cause of unilateral ocular pain and headache, especially in young population. In this study, we implemented a survey and examined the eyes of patients who used smartphones with 20/20 vision. The patients with normal neurologic and ear-nose-throat (ENT) examination findings comprised the study group. The age, duration of smartphone use, ocular examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Studies have also shown the adverse effects of smartphones addiction on quality of sleep [5], physical activity [8] and academic performance [9]. Smartphones addiction also have harmful physical consequences like headache, blurred vision, neck and shoulder pain and impairment of hand function [10][11][12]. There are not enough available researches about smartphones addiction among young people in Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown the adverse effects of smartphones addiction on quality of sleep [5], physical activity [8] and academic performance [9]. Smartphones addiction also have harmful physical consequences like headache, blurred vision, neck and shoulder pain and impairment of hand function [10][11][12]. There are not enough available researches about smartphones addiction among young people in Egypt.…”
Section: Introductionmentioning
confidence: 99%